Management of Unilateral Masseter Hypertrophy and Hypertrophic Scar—A Case Report. (10th July 2012) - Shetty, Naresh; Malaviya, Rajanikanth K.; Gupta, M. K.
Abstract : Masseter muscle hypertrophy is a rare condition of idiopathic cause. It clinically presents as an enlargement of one or both masseter muscles. Most patients complain of facial asymmetry; however, symptoms such as trismus, protrusion, and bruxism may also occur. Several treatment options reported for masseter hypertrophy are present, which range from simple pharmacotherapy to more invasive surgical reduction. Keloid scar with unilateral masseter hypertrophy is a rarely seen in clinical practice. This paper reports a case of unilateral masseter hypertrophy with keloid scar in the angle of the mandible for which surgical treatment was rendered to the patient by using a single approach.